2012
DOI: 10.1002/pon.3162
|View full text |Cite
|
Sign up to set email alerts
|

‘It's all bad news’: the first 3 months following a diagnosis of malignant pleural mesothelioma

Abstract: Objective: This study explores patient's experience during the first three months following a diagnosis of malignant pleural mesothelioma.Methods: This study uses a grounded theory approach with semi-structured, face-toface interviews with ten patients during the first 3 months following diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 19 publications
1
85
0
1
Order By: Relevance
“…First-degree relatives reported lower opinions of others, a greater belief that goals cannot be reached or problems solved, support for the notion that they are indecisive and were more likely to suffer from fear that significantly inhibited normal activities than were healthy controls. Arber and Spencer 167 interviewed 10 patients with MPM from two hospitals in the South of England 167 . All participants reported high levels of uncertainty and feelings of a lack of control leading to psychosocial distress since receiving their diagnosis.…”
Section: Section 14: Care and Managementmentioning
confidence: 99%
“…First-degree relatives reported lower opinions of others, a greater belief that goals cannot be reached or problems solved, support for the notion that they are indecisive and were more likely to suffer from fear that significantly inhibited normal activities than were healthy controls. Arber and Spencer 167 interviewed 10 patients with MPM from two hospitals in the South of England 167 . All participants reported high levels of uncertainty and feelings of a lack of control leading to psychosocial distress since receiving their diagnosis.…”
Section: Section 14: Care and Managementmentioning
confidence: 99%
“…Among papers that focus on exposed subjects, eight are quantitative in nature, one is an exposed vs non exposed study, two are nested studies, and five are cross‐sectional studies . Psychological interventions have been analyzed in three studies, and one study focused on exposed subjects . The diverse nature of these studies does not allow diagnosable levels of psychopathology to be identified.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Some of the qualitative tools used in many of our sample studies include semi‐structured interviews and transcripts from psychotherapy group sessions . The psychological impact of diagnosis, the onset of physical symptoms, the distribution of risk information, lifestyle habits, coping strategies, and occupational context were the most commonly identified constructs.…”
Section: Investigative Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 495 patients,5 92% reported three or more symptoms at diagnosis with fatigue (94%), dyspnoea (89%), chest pain (85%), appetite loss (87%) and cough (75%) being the most common. The psychological burden of a diagnosis of MPM can be equally distressing with patients reporting feelings of uncertainty and lack of control 6. Carers of patients with MPM similarly report an emotional and physical toll 7.…”
mentioning
confidence: 99%